Harnessing filler materials for enhancing biogas separation membranes - Chuah, Chong Yang (2020)
Biogas is an increasingly attractive renewable resource, envisioned to secure future energy demands and help curb global climate change. To capitalize on this resource, membrane processes and state-of-the-art membranes must efficiently recover methane (CH4) from biogas by separating carbon dioxide (CO2). Composite (a.k.a. mixed-matrix) membranes, prepared from common polymers and rationally selected/engineered fillers, are highly promising for this application. This review comprehensively examines filler materials that are capable of enhancing the CO2/CH4 separation performance of polymeric membranes. Specifically, we highlight novel synthetic strategies for engineering filler materials to develop high-performance composite membranes. Besides, as the matrix components (polymers) of composite membranes largely dictate the overall gas separation performances, we introduce a new empirical metric, the "Filler Enhancement Index" ( Findex), to aid researchers in assessing the effectiveness of the fillers from a big data perspective. The Findex systematically decouples the effect of polymer matrices and critically evaluates both conventional and emerging fillers to map out a future direction for next-generation (bio)gas separation membranes. Beyond biogas separation, this review is of relevance to a broader community with interests in composite membranes for other gas separation processes, as well as water treatment applications.